Desempenho produtivo e exigências de macrominerais em carneiros Santa Inês sob restrição alimentar - Araújo Filho, Jaime Miguel de (2012)
In order to evaluate the physical characteristics and estimate the requirements of macrominerals in sheep Santa Inês under food restriction, an experiment was conducted using 32 male sheep, entire, 30 kg with initial weight body, housed individually and distributed in a completely randomized design with three treatments and eight repetitions. The treatments consisted of animals without food restriction and 30% and 60% restriction in relation to the animals of treatment without food restriction. Were evaluated intake and digestibility of nutrients, initial weight, final weight, average daily weight gain, feed efficiency and nitrogen balance for the performance test, the fasted live weight, empty body weight, hot carcass weight and cold, biological incomes, commercial and hot carcass, conformation, finishing, pelvicorenal fat, sternum length and internal carcass, width of the previous, of thorax and croup, perimeters leg and croup, thorax depth and compactness for carcass; weight and yield of the neck, palette, ribs, leg and loin, to evaluate the commercial cuts, color, marbling, texture, thickness of subcutaneous fat, GR measure and loin eye area, to evaluate the loin; weight and yield of blood, skin, liver, respiratory apparatus, heart, head, feet, reproductive apparatus, gallbladder, bladder, omentum fat of, stomachs, intestines, spleen, kidney and pelvic fat and kidney, to evaluate the non-components housing; and, body composition in calcium, phosphorus, potassium and magnesium, to estimate the net requirements for gain and maintenance of rams. The food restriction favored a higher digestibility of fibrous carbohydrates and an nitrogen balance reduced. Considering the carcass characteristics, the restriction did not affect income biological, commercial, hot carcass and cuts of higher biological value and can be used moderately by 30% in an attempt to reduce production costs without affecting the income and carcass quality of Santa Ines sheep. Sheep submitted the moderate dietary restriction (30%), decreased the yield of the liver, but this restriction did not affect the income of other carcass non-components. So, this level can be used as a tool to reduce feed costs without compromising the yield of non-components carcass of Santa Ines sheep. The values of body composition calcium ranged from 22,04 to 25,52 g, of phosphorus 9,86 to 9,95 g, of potassium from 1,49 to 1,46 g, and magnesium 0,88 to 1,06 g per kg of body weight empty. The net calcium, phosphorus, potassium and magnesium for the gain ranged from 18,7 to 21,7 g, 8,4 to 8,5 g, 1,3 to 1,2 g and 0,7 to 0,9 g per kg day body weight, respectively, to Santa Inês rams of 30 the 45 kg of body weight. The requeriments for maintenance on Santa Inês rams weighing 30 to 45 kg of body weight was 361 mg calcium, 274 mg phosphorus, 61 mg potassium and 34 mg of Mg per day.